Manuka Honey: Feasibility and Safety in Postoperative Neurosurgical Wound Care. (May 2021) - Felbaum, Daniel R.; Dowlati, Ehsan; Jacobs, Matthew; Tom, Laura K.
ABSTRACT: OBJECTIVE: To date, no reports have been published on active Leptospermum manuka honey (ALH) feasibility as a postoperative topical wound supplement in neurosurgical patients. The objective of the study is to present the authors' initial experience with using ALH in postoperative neurosurgical patients. METHODS: A single-surgeon retrospective case series review of cranial and spinal operations between 2018 and 2020 was performed in patients with nonhealing wounds or wounds deemed "at risk" as defined by grade 1 Sandy surgical wound dehiscence grading classification. An ALH gel or ointment was applied to these incisions once a day for 2 to 4 weeks. Patients were followed up in the clinic every 2 weeks until incisions had healed. RESULTS: Twenty-five postoperative patients (12 cranial, 13 spinal) were identified to be at high risk of operative debridement. All 25 patients were prescribed a topical application of ALH, which was easily adopted without patient-related adverse events. Seven (four cranial, three spinal) patients required operative debridement and treatment with long-term antibiotic therapy. CONCLUSIONS: In this small case series of neurosurgical patients who were at risk of poor wound healing, the application of medical-grade ALH was well tolerated without patient-reported adverse events. The ALH may have prevented the need for operative debridement in the majority of patients. Further prospective studies are necessary to establish its efficacy in wound healing in the neurosurgical population.